Filtration performances of HVAC filters for PM10 and microbial aerosols— Influence of management in a lab-scale air handling unit. Issue 6 (2nd June 2016) - González, Luisa F.; Joubert, Aurélie; Andrès, Yves; Liard, Myriam; Renner, Christophe; Le Coq, Laurence
ABSTRACT: Filtration performances of air handling unit (AHU) filters for particles and microbial aerosols were investigated. The influence of the AHU operational conditions on the behavior of microorganisms collected on the filters was also studied. A lab-scale AHU with two filtration stages was developed and validated for the study of downsized filters with industrial geometries. Three types of filters of different efficiency were considered: G4, F7, and F9, according to European standard EN 779. Two configurations of filters were studied: G4 pleated/F7 bag and F7/F9 bag. Filters were sequentially clogged by alumina particles, which provided a mineral fraction in the particulate cake, and then by micronized rice particles, which provided the fungus Penicillium chrysogenum and an organic fraction that acts as a substrate for microorganisms. Finally, a microbial aerosol composed of endospores of Bacillus subtilis and spores of Aspergillus niger was nebulized to contaminate filters. After clogging, periods of 5 days on and 2 day weekend stops with restarts of ventilation were simulated for 6 weeks. The results showed that the filter efficiency for particles was quite comparable to that for microbial aerosols expressed in cultivable concentration. The particulate cake composed of alumina and micronized rice particles enabled the growth of the endogenous species P. chrysogenum and the survival of exogenous species B. subtilis and A. niger on filters. During restarts of ventilation, low particle concentrations were detected downstream of the second filtration stages by release but the microbial concentration from the fraction of air sampled was below the detection limit. Copyright © 2016 American Association for Aerosol Research